Three essays on the environmental Kuznets curve for water pollution - Thompson, Alexi (Kansas State University, 2012)
This dissertation is composed of three chapters each investigating the Environmental Kuznets Curve (EKC) for water pollution. The first chapter looks at downstream dependence, the second chapter looks at the effect water abundance has on an EKC for water pollution, and the third chapter looks at different ways to control for population across countries in an EKC empirical model. Of particular note a theoretical model is developed in the first chapter that links directly with the empirical EKC model and marginal effects of consumption and effort on pollution are derived. This model specification may be particularly useful in future EKC studies. In general, there is some evidence of an EKC although it appears to depend on the country.
Keywords: Environmental Kuznet's Curve; Environmental economics (0438)